Search for sub-eV axion-like particles in a quasi-parallel stimulated resonant photon-photon collider with “coronagraphy” - The SAPPHIRES collaboration; Yuri Kirita; Airi Kodama; Kensuke Homma; Catalin Chiochiu; Mihai Cuciuc; Georgiana Giubega; Takumi Hasada; Masaki Hashida; ShinIchiro Masuno; Yoshihide Nakamiya; Liviu Neagu; et al. (Journal of High Energy Physics)
Abstract Axion-like particles (ALPs) have been searched for with a quasi-parallel stimulated resonant photon-photon collider sensitive to the sub-eV mass range by focusing two-color near-infrared pulse lasers into a vacuum. In this work, we have developed a specialized coronagraphy to mitigate the dominant background photons from optical elements by introducing an eclipse filter. The observed number of signal-like photons was found to be consistent with residual background photons from optical elements through an additional test by degrading the focal point overlapping factor between the two lasers. We then extended the exclusion region in the relation between ALP-photon coupling, g/M, and the ALP mass m, reaching the most sensitive point g/M = 5.45 × 10 −7 GeV −1 at m = 0.15 eV for pseudoscalar ALPs.